The Role of Language Teacher Associations in Professional Development (Second Language Learning and Teaching, 2018)
Providing a timely and much-needed resource on LTAs, the book helps readers recognize the importance and nature of teachers' professional development, while also contributing to the process of educational change. In order to achieve a suitable level of educational and policy change, a research base for LTAs is called for. This book represents a step in the right direction, introducing readers to essential research on the central role of LTAs in language teachers' development. Although pre-service and in-service education programs, to be found at government and/or private institutions, are of great value, it is impossible to prepare teachers for all the challenges they will face throughout their careers. In response, many professional associations also provide a wide range of professional development activities for their teacher members. The book will be of interest to language teachers, graduate students, teacher educators and researchers, educational leaders and policymakers, as well as teacher associations.